Pendampingan Pemanfaatan Teknologi Informasi dengan Aplikasi Quiziz dalam Pembelajaran Bahasa Inggris di SMA Islam Arahamniyah Desa Mujur Kecamatan Praya Timur: Assistance in the Utilization of Information Technology with the Quizizz Application in English Language Learning at Arahamniyah Islamic High School, Mujur Village, Praya Timur District - Bakri, Umar; Ozi Satria; Rijnan (Indonesia, 2025)
The rapid development of technology makes teachers have to innovate in the teaching process. Of course, by utilizing technology in the learning process, students can compete with other countries. This community service (PkM) aims to assist Arahamniyah Islamic High School students in Mujur Village, East Praya District, in using digital technology to learn English. This activity is hoped to increase students' interest, motivation, and ability to master English by utilizing relevant digital platforms and tools. The methods used include intensive assistance to students and teachers, with a focus on the use of English learning applications, interactive media, and online learning resources. The expected results of this program are the creation of a more dynamic, creative, and effective learning environment, as well as increasing students' English competency. Apart from that, this program is also expected to equip teachers with the skills to integrate digital technology into the learning process. Thus, this activity not only has a positive impact on students but also supports the development of teacher professionalism in facing educational challenges in the digital era.